First Report of CRISPR/Cas9 Gene Editing in Castanea sativa Mill - Pavese, Vera; Moglia, Andrea; Corredoira, Elena; Martínez, Mª Teresa; Torello Marinoni, Daniela; Botta, Roberto (Frontiers in Plant Science, 2021)
CRISPR/Cas9 has emerged as the most important tool for genome engineering due to its simplicity, design flexibility, and high efficiency. This technology makes it possible to induce point mutations in one or some target sequences simultaneously, as well as to introduce new genetic variants by homology-directed recombination. However, this approach remains largely unexplored in forest species. Here, we report the first example on CRISPR/Cas9-mediated gene editing in Castanea genus. As a proof of concept, we targeted the gene encoding phytoene desaturase (pds), whose mutation disrupts chlorophyll biosynthesis allowing for visual assessment of knockout efficiency. Globular and early torpedo-stage somatic embryos of C. sativa (European chestnut) were co-cultured for 5 days with a CRISPR/Cas9 construct targeting two conserved gene regions of pds and subsequently cultured on selection medium with kanamycin. After eight weeks of subculture on selection medium, 4 kanamycin resistant embryogenetic lines were isolated. Genotyping of these lines through target Sanger sequencing of amplicons revealed the successful gene editing. Cotyledonary somatic embryos were maturated on maltose 3% and cold-stored at 4ºC for 2 months. Subsequently, embryos were subjected to the germination process to produce albino plants. This work opens the way to the use of the CRISPR/Cas9 system in European chestnut for biotechnological applications.